Survey on test case generation, selection and prioritization for cyber‐physical systems. (15th September 2021) - Sadri‐Moshkenani, Zahra; Bradley, Justin; Rothermel, Gregg
Summary: A cyber‐physical system (CPS) is a collection of computing devices that communicate with each other, operate in the target environment via actuators and interact with the physical world through sensors in a feedback loop. CPSs need to be safe and reliable and function in accordance with their requirements. Testing, focusing on a CPS model and/or its code, is the primary approach used by engineers to achieve this. Generating, selecting and prioritizing test cases that can reveal faults in CPSs, from the wide range of possible input values and stimuli that affect their operation, are of central importance in this process. To date, however, in our search of the literature, we have found no comprehensive survey of research on test case generation, selection and prioritization for CPSs. In this article, therefore, we report the results of a survey of approaches for generating, selecting and prioritizing test cases for CPSs; the results illustrate the progress that has been made on these approaches to date, the properties that characterize the approaches and the challenges that remain open in these areas of research. Abstract : Testing Cyber‐Physical Systems (CPSs) is the primary approach used to achieve safety and reliability, and assure that CPSs function in accordance with their requirements. This article reports 1) the progress to date on approaches for generating, selecting, and prioritizing CPS, which is of central importance in testing CPSs, 2) the properties that characterize the approaches, and 3) the challenges that remain open in these areas of research.